1999
DOI: 10.1159/000010092
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Acceptance of Outpatient Hysteroscopy

Abstract: There is a trend towards performing hysteroscopy and endometrial biopsy on an outpatient basis, as this alleviates the need for both an inpatient stay and a general anesthesia. Despite the wide acceptance by medical staff, there are few publications on how patients actually tolerate and accept these procedures. We performed a survey on 185 patients attending the outpatient hysteroscopy clinic at a teaching hospital to assess the degree of pain and their acceptance to those procedures using a visual analogue sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 7 publications
1
20
1
3
Order By: Relevance
“…The women in this study showed an increase in the pain score, still not statistically significant, but since the biopsy was performed only in 62.1% of the group, and this study was not designed to evaluate biopsy as the main factor, probably the sample group was not high enough to measure the effect of that outcome (4) . It is supposed that a greater acceptance could be reached offering to the patients a detailed explanation of the method, reducing anxiety and expectation (6,12) , but this study showed that the patients who had been previously informed by their doctors about the procedure did not experience any relief in their discomfort. Those submitted to hysteroscopy once before, who knew all steps of the exam, even referred worse pain than those undergoing their first exam.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The women in this study showed an increase in the pain score, still not statistically significant, but since the biopsy was performed only in 62.1% of the group, and this study was not designed to evaluate biopsy as the main factor, probably the sample group was not high enough to measure the effect of that outcome (4) . It is supposed that a greater acceptance could be reached offering to the patients a detailed explanation of the method, reducing anxiety and expectation (6,12) , but this study showed that the patients who had been previously informed by their doctors about the procedure did not experience any relief in their discomfort. Those submitted to hysteroscopy once before, who knew all steps of the exam, even referred worse pain than those undergoing their first exam.…”
Section: Discussionmentioning
confidence: 65%
“…Outpatient diagnostic hysteroscopy and endometrial sampling replaced the uterine curettage as the gold standard investigation method for abnormal uterine bleeding and endometrial conditions, providing a precise evaluation of the intrauterine cavity, besides other obvious advantages of no need to use anesthesia or hospitalization (6) . According to different authors, pain is the main limiting factor to the outpatient procedure and one of the causes of impaired accuracy of the exam, sometimes leading to unsatisfactory results (1,(4)(5) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the main limitation to the widespread use of outpatient procedures is pain [9]. Therefore, over the past 20 years, there has been a trend towards assessing and performing some procedures in outpatients [10]. Outpatient procedures are associated with fewer anaesthetic risks, reduced hospital admissions, easy access and quick recovery, with no increase in postoperative analgesia [9].…”
Section: Introductionmentioning
confidence: 99%